The global governance of knowledge : patent offices and their clients - Drahos, Peter, 1955- (Cambridge [England] : Cambridge University Press, 2010)
'Patent offices around the world have granted millions of patents to multinational companies. Patent offices are rarely studied and yet they are crucial agents in the global knowledge economy. Based on a study of forty-five rich and poor countries that takes in the world's largest and smallest offices, Peter Drahos argues that patent offices have become part of a globally integrated private governance network, which serves the interests of multinational companies, and that the Trilateral Offices of Europe, the USA and Japan make developing country patent offices part of the network through the strategic fostering of technocratic trust. By analysing the obligations of patent offices under the patent social contract and drawing on a theory of nodal governance, the author proposes innovative approaches to patent office administration that would allow developed and developing countries to recapture the public spirit of the patent social contract'--Provided by publisher.
Machine generated contents note: 1. Patent offices and the global governance of knowledge; 2. Labyrinths and catacombs: patent office procedure; 3. The rise of patent offices; 4. The sun and its planets - the European Patent Office and National Offices; 5. The USPTO and JPO; 6. The age of trilaterals and the spirit of co-operation; 7. The jewel in the crown - India's Patent Office; 8. The dragon and the tiger: China and South Korea; 9. Joining the patent office conga line: Brazil; 10. Islands and regions in the patent stream; 11. Reclaiming the patent social contract; 12. Patent administration sovereignty - nodal solutions for small countries, developing countries.
Includes bibliographical references and index.
Keywords: Patent laws and legislation; Globalization